Comparing the Involvment of Academic Librarians in the Cycical Review Process for Graduate Programs in the Humanities and in the sciences - Bowker, Lynne (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2019)
In Ontario, all graduate programs at publicly assisted universities must be reviewed on a cyclical basis at least once every eight years. This paper adopts a corpus-based approach to investigate and compare how academic librarians are integrated into the cyclical review process for graduate programs in the Humanities and graduate programs in the Sciences. Findings reveal that these two broad disciplinary cultures differ in the way and the degree to which they recognize libraries and involve librarians in the program review process.